2015
DOI: 10.12930/nacada-15-026
|View full text |Cite
|
Sign up to set email alerts
|

Strengthen the Bond: Relationships Between Academic Advising Quality and Undergraduate Student Loyalty

Abstract: Extant research suggests that student loyalty, a strong bond between the student and university, positively affects important student outcomes, most notably retention. In this article, we advance the notion that academic advisors should become managers of the student–university relationship. We examine the correlation between respondents' perceived quality of academic advising and their loyalty to the university as measured by our recently developed Student University Loyalty Instrument, administered to 1,207 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 21 publications
1
25
0
Order By: Relevance
“…As Hunter and White () explain, “Academic advising, well developed and appropriately accessed, is perhaps the only structured campus endeavor that can guarantee students sustained interaction with a caring and concerned adult who can help them shape such an experience” (p. 21). Research supports the notion that advisor–advisee relationships can positively affect students’ connection to their institutions and their academic success (Drake ; Light ; Vianden ; Vianden and Barlow ; Young‐Jones et al. ).…”
Section: Rethinking the Job Of Advisingmentioning
confidence: 70%
“…As Hunter and White () explain, “Academic advising, well developed and appropriately accessed, is perhaps the only structured campus endeavor that can guarantee students sustained interaction with a caring and concerned adult who can help them shape such an experience” (p. 21). Research supports the notion that advisor–advisee relationships can positively affect students’ connection to their institutions and their academic success (Drake ; Light ; Vianden ; Vianden and Barlow ; Young‐Jones et al. ).…”
Section: Rethinking the Job Of Advisingmentioning
confidence: 70%
“…For example, Metzner (1989) showed that academic advising services have both direct and indirect effects on student retention. A more recent study by Vianden and Barlow (2015) revealed student's perception of quality advising has a positive association with student's loyalty, an indicator of retention. However, while student retention and satisfaction are important student outcomes, they cannot adequately measure students' learning and development.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most empirical studies of academic advising have traditionally focused on the influence of academic advising on students' retention and satisfaction (e.g., Beal & Noel, 1980;Fielstein & Lammers, 1992;Metzner, 1989;Vianden & Barlow, 2015;Waggenspack & Hensley, 1992). For example, Metzner (1989) showed that academic advising services have both direct and indirect effects on student retention.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A high level of engagement is especially important at high enrollment, research-intensive institutions. Even though a strong connection between student and adviser has implications for multiple positive student outcomes (Vianden & Barlow, 2015), students often report dissatisfaction with the academic advising they receive (Allen & Smith, 2008: Keup & Stolzenberg, 2004.…”
Section: Abstract: Academic Advising Administration Undergraduatesmentioning
confidence: 99%